Contrapuntos en la agricultura de Galicia - Torres Luna, María Pilar de (Investigaciones Geográficas, 1993)
Galicia gets individualized in the context of the Spanish countrycide ar being a unique space, both for its working population ar well as for the high number of cultivations found in it. The cattle-raising is the most important activity in the agricultural domain. Besider cattle then are ‘islands” of evolutioned agriculture, modernized and commercialized, that provide hign yields and benefits. On the other hand, the largest spaces are dedicated to fodder cultivations, following in importance maize, potato, cereal and vine. This article deals with some of those interverting contrasts in the galician agriculture.